The Role of Christian Education in Preventing and Addressing the Crisis Caused by Online Gambling - Zalukhu, Amirrudin (PEADA': Jurnal Pendidikan Kristen, 2025)
Abstract: The growing prevalence of online gambling has triggered severe economic and spiritual crises, affecting individuals, families, and communities. This study aims to analyze the role of Christian education in preventing and addressing the destructive impacts of online gambling through a qualitative literature review. Grounded in theological principles and educational theory, Christian education emphasizes core values such as stewardship, self-control, and accountability as foundations for character formation and behavioral prevention. It serves not only as a preventive mechanism but also as a means of recovery by offering spiritual counseling, financial literacy training, and holistic community support. This study employs a qualitative-descriptive method by analyzing relevant theological, pedagogical, and psychosocial literature. The findings reveal that Christian education holds significant transformative potential in integrating moral development, economic stability, and spiritual restoration for individuals affected by online gambling. Key challenges include cultural resistance to faith-based values and limited collaboration between Christian institutions and secular organizations. Nevertheless, opportunities exist to expand Christian education curricula to address contemporary digital issues more contextually. In conclusion, the study affirms that value-based Christian education is not only relevant but essential in responding to the multidimensional crises caused by online gambling. It recommends the development of contextual educational models and further research to assess the long-term impact of such interventions. Keywords: Christian Education; online gambling; economic crisis; spiritual crisis